Attitudes in a post-war context: Majority and minority intergroup attitudes in a divided community - Čorkalo Biruški, Dinka (Array, 2008)
Social context is one of key factors in attitudes formation and change. This is particularly true for inter-group attitudes. Their manifestation is a subject of an overt social influence but also of a subtle social tuning of specific social cues that determines desirability of expression of a particular attitude. When a community is fundamentally divided according to the ethnic key, other social cues may be of less importance. As a result of the recent war, the city of Vukovar (Croatia) turned into the ethnically divided community where even schools became divided along the ethnic lines. The present study explores a set of group relevant attitudes in the context of everyday realities of this divided community. We assessed a set of attitudes relevant for the context of current separate schooling: (1) attitudes towards school integration ; (2) attitudes toward social integration of children outside the schools ; (3) tolerance of diversity ; (4) attitudes toward assimilation of ethnic minorities. Two independent samples of school children of Croatian and Serbian ethnic background (N= 719 and N= 815) aged 12-16 and their parents participated in the study at two points in time: in 2001. and 2007. Results revealed different pattern of attitudes depending on the majority and minority status at both time points. The majority/minority status was relevant when congruence between parental and children’ s attitudes was assessed. The results are discussed in light of complexities of inter-group relations in the post-war context, bearing in mind different social influences on children’ s attitudes, and their possible implications for the future inter-ethnic relations in the community.